2017
DOI: 10.1177/1941738117747868
|View full text |Cite
|
Sign up to set email alerts
|

Expected Time to Return to Athletic Participation After Stress Fracture in Division I Collegiate Athletes

Abstract: Background:Few studies have documented expected time to return to athletic participation after stress fractures in elite athletes.Hypothesis:Time to return to athletic participation after stress fractures would vary by site and severity of stress fracture.Study Design:Retrospective cohort study.Level of Evidence:Level 3.Methods:All stress fractures diagnosed in a single Division I collegiate men’s and women’s track and field/cross-country team were recorded over a 3-year period. Site and severity of injury wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 21 publications
(32 reference statements)
0
23
0
5
Order By: Relevance
“…In pre-professional dancers, BSI can represent up to 19% of injuries over an academic year, with tibial stress fractures taking the longest time to return to full dance [ 17 ]. When managed conservatively, tibial BSI may require 6–27 weeks to return to sport depending on severity [ 2 , 25 , 26 ].…”
Section: Epidemiology Of Bone Stress Injuries In Adolescent Athletesmentioning
confidence: 99%
See 1 more Smart Citation
“…In pre-professional dancers, BSI can represent up to 19% of injuries over an academic year, with tibial stress fractures taking the longest time to return to full dance [ 17 ]. When managed conservatively, tibial BSI may require 6–27 weeks to return to sport depending on severity [ 2 , 25 , 26 ].…”
Section: Epidemiology Of Bone Stress Injuries In Adolescent Athletesmentioning
confidence: 99%
“…For the lumbar spine, a brace may reduce pain during activities of daily living; however, efficacy is yet to be confirmed [ 39 , 137 ]. Time to return to unrestricted sport for any BSI in collegiate level athletics is reportedly 12–13 weeks on average, depending on the grade and severity, yet may range from 6 to 30 weeks [ 25 , 50 ], and is highly dependent on the location of injury.…”
Section: Management and Rehabilitationmentioning
confidence: 99%
“…Some runners then choose to rest or quit running entirely, which leads to time lost from running, reduced mileage, impaired race performance, decreased fitness, and potential overall health consequences. 3,5 To treat this prevalent running injury, we must understand how runners with ERLLP differ from their healthy counterparts. Unfortunately, the causes of ERLLP are not firmly established, although some risk factors have been identified.…”
mentioning
confidence: 99%
“…Special attention in both future research and clinical practice should also be focused on identification of inflammatory conditions of the foot, given the prevalence of foot injuries in this population and that stress injuries of the foot can be both subtle in presentation and result in long periods of TL. [13][14][15] The most reported injuries during this period were hamstring tears and lateral ligament complex tears (ankle sprains). Authors of previous studies have indicated that hamstring injuries in this population are potentially attributable to the strain imposed during active lengthening.…”
Section: Discussionmentioning
confidence: 99%